2004
DOI: 10.1002/jez.a.74
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and mRNA expression of a FTZ‐F1 homologue from the pituitary of the orange‐spotted grouper, epinephelus coioides

Abstract: A FTZ-F1 homologue was cloned from the pituitary cDNA library of the orange-spotted grouper. The full-length cDNA of the orange-spotted grouper FTZ-F1 spanned 1735 bp including a poly (A) tail. The open reading frame encodes a protein of 468 amino acids. Sequence analysis indicated that it had a structure typical of the orphan nuclear receptor superfamily, and the FTZ-F1 box, a characteristic of the FTZ-F1 family. Phylogenetic analysis indicated that the orange-spotted grouper FTZ-F1 was closely related to med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Multiple forms of FTZ-F1 have been reported across vertebrate phyla that includes four isoforms in zebrafish [15] , [21] , [31] and two isoforms in the arctic char [17] , [32] , frog [33] and chicken [27] . In the present study, only a single form of FTZ-F1 was obtained similar to rainbow trout [25] , medaka [18] and orange spotted grouper [34] . The deduced amino acid sequence and phylogenetic analysis of catfish FTZ-F1 showed identity with NR5A1 genes.…”
Section: Discussioncontrasting
confidence: 60%
“…Multiple forms of FTZ-F1 have been reported across vertebrate phyla that includes four isoforms in zebrafish [15] , [21] , [31] and two isoforms in the arctic char [17] , [32] , frog [33] and chicken [27] . In the present study, only a single form of FTZ-F1 was obtained similar to rainbow trout [25] , medaka [18] and orange spotted grouper [34] . The deduced amino acid sequence and phylogenetic analysis of catfish FTZ-F1 showed identity with NR5A1 genes.…”
Section: Discussioncontrasting
confidence: 60%
“…NR5A1 are key regulators of steroidogenesis and are involved in the testis determining pathway (Ikeda et al 1993(Ikeda et al , 1994Sadovsky et al 1995). A FTZ-F1 homologue was cloned from the pituitary cDNA library of the Fish Physiol Biochem (2010) 36:181-193 189 orange-spotted grouper (Zhang et al 2004b). The expression of FTZ-F1 in the gonad decreased significantly in response to MT treatment for 40 days and 60 days, but its expression in the pituitary was not altered significantly.…”
Section: Molecular Mechanisms On Sex Change In Groupersmentioning
confidence: 99%
“…Our previous study showed that the orange-spotted grouper cyp19a1a promoter had two conserved Ftz-f1 binding sites, which could mediate the activation of cyp19a1a promoter by Ftz-f1 homologues [18]. However, a previously isolated Ftz-f1 homologue (Nr5a4) from the orangespotted grouper [19] could not activate cyp19a1a transcription in vitro [18]. In the present study, a Lrh-1 homologue is isolated from the orange-spotted grouper, and its possible involvement in the regulation of cyp19a1a in the ovary is explored.…”
Section: Introductionmentioning
confidence: 99%